Acquisition of the pulmonary venous and left atrial anatomy with non‐contrast‐enhanced MRI for catheter ablation of atrial fibrillation: Usefulness of two‐dimensional balanced steady‐state free precession. Issue 4 (23rd December 2014) - Shigenaga, Yutaka; Kiuchi, Kunihiko; Okajima, Katsunori; Ikeuchi, Kazushi; Ikeda, Takayuki; Shimane, Akira; Yokoi, Kiminobu; Teranishi, Jin; Aoki, Kousuke; Chimura, Misato; Masai, Hideyuki; Yamada, Shinichiro; et al.
Abstract: Background: Usually, the pulmonary venous and left atrial (PV–LA) anatomy is assessed with contrast‐enhanced computed tomographic imaging for catheter ablation of atrial fibrillation (AF). A non‐contrast‐enhanced magnetic resonance (MR) imaging method has not been established. Three‐dimensional balanced steady‐state free precession (3D b‐SSFP) sequences cannot visualize the PV–LA anatomy simultaneously because of the signal intensity defect of pulmonary veins. We compared two‐dimensional (2D) b‐SSFP sequences with 3D b‐SSFP sequences in depicting the PV–LA anatomy with non‐contrast‐enhanced MR imaging for AF ablation. Methods: Eleven healthy volunteers underwent non‐contrast‐enhanced MR imaging with 3D b‐SSFP and 2D b‐SSFP sequences. The MR images were reconstructed on the 3D PV–LA surface image. Two experienced radiological technicians independently scored the multiplanar reformatted (MPR) images on a scale of 1–4 (from 1, not visualized, to 4, excellent definition). The overall score was a sum of 5 segments (LA and 4 PVs). Results: In the 2D b‐SSFP method, MR imaging was successfully performed, and the 3D PV–LA surface image was precisely reconstructed in all healthy volunteers. The image score was significantly higher in the 2D b‐SSFP method compared to the 3D b‐SSFP method (19 [19; 20] vs. 12 [11; 15], p =0.004, for both observers). No PV signal intensity defects occurred in the 2D b‐SSFP method. Conclusions: The 2D b‐SSFP sequence was more useful than the 3D b‐SSFP sequence in adequately depicting the PV–LA anatomy.